SLEEP HYGIENE IN ADOLESCENTS - Iwan Purnawan; Ikit Netra Wirakhmi (Pedagogic Research-Applied Literacy Journal, 2024)
Adolescent health is crucial for developing a productive future generation, with sleep quality being a key component. Many adolescents struggle with sleep issues due to academic pressure, excessive gadget use, and poor habits. This community service project aimed to improve sleep hygiene awareness among students at MTS Ma'arif 2 Ajibarang through leaflet distribution. On April 30, 2024, 150 sleep hygiene leaflets were distributed to students. Feedback was gathered from students and teachers to evaluate engagement and understanding. The leaflets were well-received. The leaflet distribution effectively raised awareness about sleep hygiene among adolescents. Future studies should assess the long-term impact of such interventions on sleep behaviors and health outcomes.